2014
DOI: 10.1016/j.celrep.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Deregulated G1/S Transcription Depends on Critical G1/S Regulon Genes to Prevent Catastrophic Genome Instability

Abstract: Expression of a G1/S regulon of genes that are required for DNA replication is a ubiquitous mechanism for controlling cell proliferation; moreover, the pathological deregulated expression of E2F-regulated G1/S genes is found in every type of cancer. Cellular tolerance of deregulated G1/S transcription is surprising because this regulon includes many dosage-sensitive proteins. Here, we used the fission yeast Schizosaccharomyces pombe to investigate this issue. We report that deregulating the MBF G1/S regulon by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 59 publications
1
16
1
9
Order By: Relevance
“…The MBF complex contains additional components, like the activator Rep2 [6] and the repressor complex formed by Nrm1 and Yox1 [7][8][9][10]. The cell cycle-dependent expression of cdc22 and cdc18 is disrupted in strains with impaired MBF function, whereas the hyperactivation of MBF induces extremely high levels of cdc18 and cdc22 mRNA, leading to over-replication of DNA [12]. The cell cycle-dependent expression of cdc22 and cdc18 is disrupted in strains with impaired MBF function, whereas the hyperactivation of MBF induces extremely high levels of cdc18 and cdc22 mRNA, leading to over-replication of DNA [12].…”
Section: Introductionmentioning
confidence: 99%
“…The MBF complex contains additional components, like the activator Rep2 [6] and the repressor complex formed by Nrm1 and Yox1 [7][8][9][10]. The cell cycle-dependent expression of cdc22 and cdc18 is disrupted in strains with impaired MBF function, whereas the hyperactivation of MBF induces extremely high levels of cdc18 and cdc22 mRNA, leading to over-replication of DNA [12]. The cell cycle-dependent expression of cdc22 and cdc18 is disrupted in strains with impaired MBF function, whereas the hyperactivation of MBF induces extremely high levels of cdc18 and cdc22 mRNA, leading to over-replication of DNA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Like its metazoan functional analog (pRB/E2F), the regulated activity of this complex is essential for the normal G1/S transition: cells with hypoactive MBF complex are unable to complete S phase while cells with hyperactive MBF show genomic instability. 8,24 When DNA replication is challenged (i.e., after treating cells with HU), fission yeast cells activate their effector kinase (Cds1) and, among many other effects, are able to maintain a high level of MBF-dependent transcription. 11 To better understand how MBF is activated at the onset of each cell cycle, we have carried out a screening aiming to isolate non-essential genes that regulate MBF activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Yox1 binds the MBF complex through the co-repressor Nrm1, mainly at the end of S phase and during G2, when MBF-dependent transcription is down-regulated. [8][9][10][11] However, when DNA replication is challenged (i.e., treatment with hydroxyurea), Yox1 is phosphorylated by the effector kinase of the DNA synthesis checkpoint, Cds1. Once phosphorylated, Yox1 is released from MBF and MBF-dependent transcription is activated until cells overcome the block to DNA replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact defects remain to be established, data suggests that persistent expression of G1/S targets during S phase results in genome instability in both yeast and mammalian cells ([102,118] and unpublished data). This suggests an important role for the repression of G1/S transcription outside of the G1 to S phase transition and, perhaps, after recovery from DNA replication stress.…”
Section: Regulation Of the Transcriptional Responsementioning
confidence: 99%